PENDAMPINGAN BUDIDAYA JAGUNG MANIS MELALUI PRAKTEK DEMONSTRASI PLOT DENGAN APLIKASI ELISITOR BIOSAKA - Ajang Maruapey; Akhmad Ali; Rajab Lestaluhu; M. Saleh Refra; Nurlela Nurlela; Selvia Tharukliling (Universitas Islam Sumatear Utara, 2023)
Assistance in the practice of demonstration plots aims in addition to measuring the skills and capacity of farmers towards the adopted cultivation technology, as well as encourage farmers to return to nature by using Biosaka from natural materials (leaves) available in the surrounding environment as a substitute for chemical fertilizers. This activity was carried out in the farmer group Cendrawasi Jl. tuturuga Klamalu Village Mariat District Sorong Regency Southwest Papua in April to June, 2023 by involving students of the Faculty of Agriculture, Muhammadiyah University of Sorong (Unamin). The method applied in community service and empowerment activities to the community or farmers is the method of learning by doing. The achievements resulting from the mentoring activities of sweet corn cultivation demonstration plot practices with Elisitor Bisosaka include making plants grow lush, healthy, increasing sweet corn production by about 50%, in addition, the use of Elisitor Biosaka can save fertilizer and pesticide costs by about 50-60 %,